1994
DOI: 10.1128/aac.38.11.2583
|View full text |Cite
|
Sign up to set email alerts
|

Postantibiotic effect of meropenem on members of the family Enterobacteriaceae determined by five methods

Abstract: The postantibiotic effect (PAE) of meropenem was determined for 11 strains, both clinical isolates and reference strains of members of the family Enterobacteriaceae. The study compares PAE results obtained by five methods used to monitor bacterial regrowth, including viable counting, alone and in combination with impedance; bioluminescence, alone and in combination with impedance; and a morphological technique. After exposure of the test organisms to meropenem (0.1 x to 100 x MIC) for 2 h, concentration-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…time of exposure and antimicrobial concentrations, may heavily influence this value. Moreover, different methodologies recently employed in assessing the PAE have produced some conflicting results [8–10]. It has been shown that the PAEs of carbapenems are highly method dependent [8] with a consistent underestimation when the viable count method is adopted instead of others such as bioluminescence or morphologic techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…time of exposure and antimicrobial concentrations, may heavily influence this value. Moreover, different methodologies recently employed in assessing the PAE have produced some conflicting results [8–10]. It has been shown that the PAEs of carbapenems are highly method dependent [8] with a consistent underestimation when the viable count method is adopted instead of others such as bioluminescence or morphologic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, different methodologies recently employed in assessing the PAE have produced some conflicting results [8–10]. It has been shown that the PAEs of carbapenems are highly method dependent [8] with a consistent underestimation when the viable count method is adopted instead of others such as bioluminescence or morphologic techniques. Recent reports have shown decreased susceptibility to carbapenems of clinical isolates of P. aeruginosa [11,12]: this resistance is conferred by the altered permeability of the outer membrane, due to the loss of D2 porin, and by the expression of chromosomal β‐lactamase.…”
Section: Discussionmentioning
confidence: 99%
“…By relating the ERT for the drug-exposed culture to the ERT for the control culture we have developed the CERT parameter, which is obtained independently of methods used to quantitate bacteria, antibiotic elimination, and growth rate (15). PAEs obtained by different methods sometimes give conflicting results (11,14,21). However, it has been shown that the use of ERT and CERT can circumvent these methodological problems (14,15).…”
mentioning
confidence: 99%
“…It has also been used and validated for quantifying the PAEs of antibiotics [4,[18][19][20][21]. This technique does not need viability counts and is not affected by changes in growth conditions from liquid to solid media, or the clumping typical of S. pyogenes, whose culture under normal conditions is a mixture of single and interlaced bacterial chains of different lengths (from 3 or 4 to 30 or 40 cells and sometimes more) [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…This period can also be a measure of the delayed regrowth of bacteria after a short period of antibiotic exposure [4].…”
Section: Introductionmentioning
confidence: 99%